Analisis Tingkat Kematangan Smart City Kabupaten Lombok Utara Menggunakan COBIT 2019 - Ari Panen Haster; Kristoko Dwi Hartomo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Indonesia's national smart city program adopts 6 main dimensions of smart cities, namely Governance, Branding, Economy, Living, Society, and Environment. The North Lombok Regency Government also developed the regional smart city concept in 2021 which is stated in the 2021-2026 RPJMD. The results of capability level research on smart city dimensions and process domains show that there are 3 dimensions that are still far from the expected target, namely Smart Branding, Smart Economy and Smart Environment, and there are 3 dimensions that are close to the achievement target, namely Smart Governance, Smart Living, and Smart Society. While the analysis of the 9 COBIT 2019 process domains shows that there are 3 process domains that have not been managed, namely: APO03, APO12 dan DSS04, 4 process domains have been defined and are running well, namely: APO07, APO12, APO14, and BAI01, and 3 process domains that have been managed and have achieved the expected targets, namely: APO07, APO14, and BAI01. The average GAP value of the analysis of smart city dimensions and COBIT 2019 process domains is 1.7 and 1.3, respectively.